Substantiation of use of Photodynamic Therapy in Experimental Research in Vitro with Strains of Periodontopathogenic Bacteria and Fungi Candida - Vadim O. Samusenkov (Journal of Global Pharma Technology, 2020)
Photodynamic therapy is used for the treatment of inflammatory periodontal diseases. This study was aimed at determining the effectiveness of the treatment of periodontitis and gingivitis with the use of a photosensitizer that interacts with the light flux, has the ability to adsorption on the surface of the bacterial cell. To determine the sensitivity of photodynamic effects, the following priority strains of microorganisms were selected: Aggregatibacter actinomycetemcomitans, Streptococcus constellatus, Candida glabrata. For the cultivation of microorganisms in the bioreactor, two types of tubes were used: 50 ml tubes with a membrane filter (TubeSpin) and 50 ml tubes of Falcon type with a lid without a membrane. 20 ml of nutrient medium was added to each tube. A. actinomycetemcomitans (37°C; RPM: 500 min‒1; measurement freq.: 3 h-1; Rev. spin period: 1 sec.; volume: 15-16 ml; λ: 850 nm); S. constellatus (37°C; RPM: 1500 min‒1; measurement freq.: 3 h-1; Rev. spin period: 2 sec.; volume: 15-16 ml; λ: 850 nm); C. albicans (37°C; RPM: 1300min‒1; measurement freq.: 3 h-1; Rev. spin period: 3sec.; volume: 15-16 ml; λ: 850 nm). After bacterial suspension inoculations, the samples were irradiated with semiconductor laser devices with different wavelengths-630 nm and 662 nm, at a power of 100 j/cm2. The basis of experimental studies was automated cultivation of isolated strains of microorganisms with control of growth curves of microbial populations using different modes of exposure and photosensitizers.Keywords: Periodontopathogenic microorganisms, Photodynamic effects, Photosensitizers, Gingivitis, periodontitis.